Mała architektura sakralna w optyce prawa polskiego i kanonicznego - Piotr Kroczek (Polonia Sacra)
In recent years one can observe in Poland the increasing numbers of investments of the churchyard crosses, roadside shrines, memorials, or plaques, that is, the objects of so-called „small sacred architecture”.